Disability, long-term care, and health care in the 21st century - Morris, Michael, 1977- (Nova Science Publishers, Inc., 2009)
Some people say that a picture is worth a thousand words. The field of management often uses a ""rich picture"" systems methodology, ""an innovative tool that encapsulates knowledge relevant to strategic reform"". It is often described in the management literature as a ""soft systems methodology"" for linking hard and soft facts in a cartoon-like representation to illustrate a complex problem simply and clearly. The following research is presented using the rich picture methodology to capture the current long-term care and long-term services and supports (LTSS) crisis. The picture and narrativ